Impacts of Climate Change on Temperature and Precipitation in Nepal: Projections and Bias Correction - Dhital, Hari Prasad; Joshi, Madhav; Budhathoki, Nabin (Journal of Sustainability and Environmental Management, 2023)
Climate change is likely to have a significant impact on Nepal, affecting its infrastructure, agriculture, and water resources. This study created day-to-day bias-corrected data of precipitation (ppt), maximum temperature (tmax) and minimum temperature (tmin) at 0.25° spatial resolution for Nepal using 7 CMIP6-GCMs under two shared socioeconomic pathways, SSP245 and SSP585. The bias-corrected datasets were produced using an empirical robust quantile mapping method for ppt and quantile mapping with linear transformation function method for tmax and tmin. The bias-corrected dataset was evaluated by comparing it against observed data for the mean values of ppt, tmax and tmin. Our bias-corrected projections reveal a warming of 4-6°C and an increase in ppt of 40-60% by the end of the 21st century. These changes will have a significant impact on Nepal’s climate, environment, and people. The bias-corrected projections can be used to assess the impact of climate change in Nepal and to develop adaptation strategies.